2001
DOI: 10.1046/j.1365-2265.2001.01246.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of gender on the short and long‐term effects of growth hormone replacement on bone metabolism and bone mineral density in hypopituitary adults: a 5‐year study

Abstract: This study demonstrates an earlier onset of GH activation of bone remodelling as reflected by S-BAP in females compared to males and confirms that long-term GH treatment in hypopituitary adults with GH deficiency increases or preserves BMD both at lumbar spine and femoral neck. However male patients seem to derive the greater benefits in BMD from long-term GH replacement; in females BMD appears simply to be stabilized rather than increased. This constitutes a genuine gender difference in susceptibility given t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 49 publications
3
51
0
Order By: Relevance
“…In men and women with GHD, dose titration according to serum IGF-I levels gave women a slightly higher total dose of GH, but men and women experienced the same reduction in central adiposity in response to treatment (17), suggesting that women are less responsive to the same total dose of GH (3,5,46). In this study, dose titration resulted in similar total daily doses of GH and produced similar increments in IGF-I in men and women.…”
Section: Discussionsupporting
confidence: 50%
“…In men and women with GHD, dose titration according to serum IGF-I levels gave women a slightly higher total dose of GH, but men and women experienced the same reduction in central adiposity in response to treatment (17), suggesting that women are less responsive to the same total dose of GH (3,5,46). In this study, dose titration resulted in similar total daily doses of GH and produced similar increments in IGF-I in men and women.…”
Section: Discussionsupporting
confidence: 50%
“…Gender may play a role in determining the response of BMD to GH replacement in adult-onset GHD. In a study of 13 patients receiving GH replacement, monitored over a median of 58 months (range 44-72), Drake et al found a significant improvement in BMD in men whereas women demonstrated stabilisation only (60). This was despite an earlier increase in serum bone-specific alkaline phosphatase (a marker of bone formation) in women than the men (60).…”
Section: Bonementioning
confidence: 84%
“…In a study of 13 patients receiving GH replacement, monitored over a median of 58 months (range 44-72), Drake et al found a significant improvement in BMD in men whereas women demonstrated stabilisation only (60). This was despite an earlier increase in serum bone-specific alkaline phosphatase (a marker of bone formation) in women than the men (60). External pituitary radiotherapy may impact on bone health, as noted in a KIMS database analysis in which pituitary irradiation was associated with reduced BMC prior to GH replacement (mean BMC 2.4 vs 2.8 kg, P!0.01) despite no difference in IGF1 SDS.…”
Section: Bonementioning
confidence: 99%
“…Markers of bone turnover are increased more rapidly in females than in males, resulting in a short-term reduction in BMD for the first 6 months following the initiation of GH therapy in both genders (Drake et al 2001b). However, BMD in men is significantly improved after prolonged therapy, whereas BMD values in women with similar baseline values remain stable (Johansson et al 1999, Drake et al 2001b). Conversely, an earlier study by Johansson et al (1996) observed lower baseline BMD values in women than in men and a correspondingly larger improvement following GH replacement in women.…”
Section: Body Compositionmentioning
confidence: 99%